The legitimation of planning processes as a challenge to metropolitan governance - Growe, Anna; Baker, Mark; Ziafati Bafarasat, Abbas (Administrative Sciences, 2020)
This study identifies three types of legitimation from the literature that can be applied within metropolitan governance in the contested sphere of spatial planning: input legitimation, throughput legitimation, and output legitimation. The reason for discussing different forms of legitimation within metropolitan governance is that, globally, only a relatively few metropolitan regions are governed directly through a single elected tier of government such as a regional council. Thus, governance mechanisms in most metropolitan regions involve some form of joint working or cross border governance initiatives that have to be legitimized in the absence of a single overarching elected council covering the whole metropolitan area. The main question discussed in this paper is, therefore, whether all three types of legitimation identified are utilized to legitimize governance mechanisms at the metropolitan scale with a specific focus-as a core part of metropolitan governance-on spatial planning processes and projects. In conceptual terms, our typology structures fuzzy lines of legitimation across the three (the "how", "who" and "what") suggested aspects of metropolitan governance in the literature. From this point, we draw on cross-case reviews of variables involved in the design, application, and outcome of input, throughput, and output legitimation in Germany and England, chosen because neither has a formal tier of metropolitan-wide government despite their differences in terms of their highly regionalised and highly centralised national government contexts respectively. This relational methodology helps us to learn about the contextual dynamics of how the three types of legitimation might reinforce one another in different international settings, leading to the overall conclusion that they will work best in combination, although output legitimation has a distinctive capacity to work in less formal settings.
Keywords: Aufsatz in Zeitschrift